LNG as a ship fuel in Iceland - Guðrún Jóna Jónsdóttir 1981- (2013)
Stricter regulations on emissions from ships within Emission Control Areas (ECA) set by the International Maritime Organization has led to increased number of ship owners around the world switching to liquefied natural gas (LNG) as a fuel. LNG is a cleaner burning and less expensive fuel than conventional oil. This thesis focuses on the benefits and disadvantages of using LNG as a ship fuel. The Icelandic fishing fleet was analyzed to evaluate if the fleet would gain from switching to LNG as a fuel. A study was conducted to assess the economic and environmental feasibility for the Icelandic ship owners to switch from Marine gas oil (MGO) to dual-fuel LNG propulsion where LNG would be used as the main fuel and MGO as a back-up fuel. Current operational cost of wetfish trawlers and pelagic vessels was compared to the estimated operational cost if the ships would switch to dual-fuel LNG propulsion to assess if the operational savings gained would pay up the investment cost needed over an acceptable time. The investment options were to convert existing ships or add to the investment cost of new ships with dual-fuel LNG propulsion. The emissions of four pollutants from the ships before and after a switch was also compared. The results of the study showed that the environmental gain would be significant. The results for the economic feasibility where dependent on the ships installed power and oil consumption as well as the different fuel price scenarios used in the study. Increased oil consumption of ships strengthens the feasibility of switching to LNG as a fuel as well as if MGO prices continues to rise in the future. The pelagic vessels showed better feasibility than the wetfish trawlers due to lower proportion of MGO required after a switch to dual-fuel LNG propulsion and higher fuel consumption. As oil prices are predicted to increase in the future, LNG as a ship fuel for the Icelandic fishing fleet could be a viable option.